Case report: a patient with thyroid storm, refractory cardiogenic shock, and cardiac arrest treated with Lugol's iodine solution and veno-arterial extra corporal membrane oxygenation support. Issue 2 (4th February 2021) - Voll, Marianne; Øystese, Kristin Astrid; Høiskar, Erik; Johansen, Odd; Nyvold, Cecilie; Norheim, Ingrid; von Lueder, Thomas G; Andersen, Geir Øystein
Abstract: Background: Thyroid storm is a life-threatening condition. Refractory cardiogenic shock and cardiac arrest are rare complications of thyroid storm and the treatment options are limited. Case summary: A 35-year- old woman treated for Grave's disease was admitted with thyrotoxicosis complicated by infection and neutropenia caused by thionamide treatment. After treatment including beta-blockers, steroids, and Lugol's iodine solution, she went into cardiac arrest. Echocardiography after resuscitation demonstrated severe biventricular heart failure. The patient was in refractory cardiogenic shock with recurrent cardiac arrest and mechanical circulatory support with a veno-arterial extra corporal membrane oxygenation (V-A ECMO) circuit was established. After 2 days on V-A ECMO and supportive treatment with iodine solution, glucocorticosteroids, and levosimendan, her myocardial function recovered and thyroid hormone levels were normalized. Veno-arterial extra corporal membrane oxygenation was discontinued, and the patient was treated with early total thyroidectomy. The patient made a full recovery with no neurological/cognitive impairment, as assessed after 4 weeks. Discussion: Adverse reactions to standard treatment of hyperthyroidism contributed to this patient's development of thyroid storm and the following refractory cardiogenic shock. When she was critically unstable, levosimendan improved myocardial function while inotropic support with dobutamine was ineffective, likely due to prolonged beta-antagonist administration. Temporary support with V-A ECMO, until effective lowering of thyroid hormone levels and improvement in myocardial function were obtained, was life-saving in this young patient and may be considered in refractory cardiogenic shock caused by thyroid storm.